A comparative study on the nanoindentation behavior, wear resistance and in vitro biocompatibility of SLM manufactured CP–Ti and EBM manufactured Ti64 gyroid scaffolds. (1st October 2019) - Ataee, Arash; Li, Yuncang; Wen, Cuie
Graphical abstract: Abstract: The present study investigates the nanoindentation behavior, wear resistance and in vitro biocompatibility of SLM manufactured CP–Ti and EBM manufactured Ti64 gyroid scaffolds and the results were compared to those of casting CP–Ti. Both the SLM- and EBM manufactured scaffolds exhibited anisotropic properties with higher reduced modulus (up to 10%) and nanohardness (up to 30%) in the transverse direction than those in building direction. The wear resistance of scaffolds in transverse direction was higher than those of in building direction by up to ∼25% and ∼82% for SLM manufactured CP–Ti and EBM manufactured Ti64 scaffolds, respectively. The SLM manufactured CP–Ti scaffolds displayed significant enhancement in wear resistance over cast dense CP–Ti with 75% lower mean worn height during a nanowear test. The coefficient of friction was varied between 0.11 and 0.24 and exhibited a steady mean value of 0.15–0.18 for CP–Ti and Ti64 scaffolds, respectively. During in vitro cell culture study, CP–Ti scaffolds showed higher cell viability and cell adhesion density in comparison to Ti64 scaffolds for all unit cell sizes. Moreover, cell adhesion density of scaffolds with smaller unit cell sizes (G2) are lower than those of larger unit cells (G3). SEM observations confirmed that both the inner space and surfaces of gyroid scaffolds provided a suitable environment for cell migration, attachment and proliferation after cell culture for 7 d. Statement of significance: It is essential to evaluate the properties of EBM/SLM manufactured scaffolds and to determine whether they can meet the tough performance requirements of the biomedical industry. In this study, nanoindentation and nanowear properties of SLM manufactured CP–Ti and EBM manufactured Ti64 gyroid scaffolds with different unit cell sizes and sample orientations were evaluated and compared to cast dense CP–Ti samples. Moreover, the in vitro biocompatibility of the scaffolds was assessed and compared to each other. To our best of knowledge, this type of study on EBM/SLM manufactured CP-Ti and Ti64 scaffolds have not been reported, to date.